Concrete skeleton structure made of unified pre-cast members for the houses in countryside - Hnidets, Bogdan (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The article describes new skeleton system dedicated for the little houses in county side. The skeleton consists of simple, unified pre-cast members, arranged in rigid frame structure. The skeleton can be disassembled and used once more.